William A. Johnson, Holt N. Parker (eds.), Ancient Literacies: The Culture of Reading in Greece and Rome - Machado, Eduardo (2011)
The German humanist Jodocus Willich (1502‐1552) published in Wittenberg 1538 a Latin translation of Physiognomonia by Pseudo Aristotle (3rd Century BC), which is preceded by a Oratio in laudem physiognomoniae that, in fact, had been the praelectio to a course about that classical work he had imparted at the University Viadrina of Frankfurt an der Oder in the summer of 1536. This text is the only known speech devoted to a systematic praise of discipline, with special emphasis on its various practical utilities: individual, social, academic, artistic, literary. Hereby, the Latin text duly corrected is presented, together with its translation into Spanish and a detailed set of notes to clarify the speech and its context as much as possible.